KH. Faqih Maskumambang's Thought Regarding the Prohibition of the Use of Kentongan as a Marker of Prayer Time: A Prophetic Hadith Perspective - Aziz Miftahus Surur; Roibin Roibin; Umi Abidah; Aris Anwaril Muttaqin; Faridhotun Nisa’ (Tribakti: Jurnal Pemikiran Keislaman, 2023)
Research on the analysis of KH. Faqih Maskumambang's thoughts on the prohibition of using the Kentongan as a prayer time marker from the perspective of the prophet's hadith needs to be conducted. The aim is to describe the understanding of hadith in the classical and contemporary eras. Kentongan is a tool commonly used by some people as a sign of prayer. The use of this tool is a part of the characteristics of Islam in the archipelago. Along with the development of knowledge, traditions have drawn the attention of many circles. The main reason for criticism and refutation is because the use of these tools is considered an act of bid'ah and resembles non-Muslim worship. Even the founding figure of the NU and KH. Hasyim Asy'ari was among those who opposed traditions. In this study, the author used a descriptive-qualitative method with a contextual approach. The primary source used the book Sharh Hazzu al-Ru'us fi Radd al-Jasus 'an Tahrim al-Naqus by KH. Faqih Maskumambang. The result of this study is that, according to KH. Faqih Maskumambang, the hadith used as the basis for the prohibition of the use of the horn is not valid. In fact, another Hadith refutes Hadith, which is more valid. In explaining this, Kyai Faqih took explanations from the Qur'an and Hadith, which have similar topics of discussion. He also takes the opinions of scholars and the methods of fiqh and logic as reinforcements.